The DARI GEROBAK KE PASAR DIGITAL: TRANSFORMASI IRT JAMUR TIRAM CRISPY MENUJU UMKM BERDAYA SAING : FROM CART TO DIGITAL MARKET: THE TRANSFORMATION OF CRISPY OYSTER MUSHROOM IRT TOWARDS COMPETITIVE MSMES - Latersia Br Gurusinga; Yusnaini Yusnaini; Hendy Hendy (LPPM Universitas Abdurrab, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a central role in the national economy, including the Kentucky Crispy Mushroom Home Industry in Medan Sunggal, which has been operating for 13 years. However, several obstacles remain, particularly in financial record-keeping, operational efficiency, and less than optimal digital marketing. This Community Service program aims to strengthen partners' capacity through mentoring in accounting, operational management, and digital marketing. The methods used include an initial survey, counseling, training, and ongoing mentoring involving lecturers and students. Implementation of this program includes the provision of production equipment such as baglog steamers, deep fryers, and continuous sealers, systematic financial record-keeping training, digital promotion strategies, and rebranding the business as